COMPARING THE EFFECTS OF LOW DOSES OF KETAMINE AND TRAMADOL IN THE PREVENTION OF POST-SPINAL ANESTHESIA SHIVERING IN CESAREAN SECTION - FARAZ , A; ISLAM , HFU; JAHANGIR , MU; ASHFAQ , F (Biological and Clinical Sciences Research Journal, 2023)
Post-spinal anesthesia (SA) shivering is a common complication following cesarean section (CS) and can pose various challenges for both patients and healthcare providers. Pethidine has been the standard treatment for this issue, but it is not recommended for nursing mothers. This study aimed to compare the efficacy of low-dosage tramadol (T), ketamine (K), and a placebo (P) in managing post-SA shivering in pregnant women undergoing CS. The objective of this study was to evaluate and compare the frequency and intensity of shivering in post-CS patients treated with low-dosage tramadol, ketamine, or placebo. Additionally, we sought to assess the impact of shivering on patients and draw conclusions about the most effective medication for shivering management in this context. A randomized, double-blind trial was conducted at the tertiary care hospital in Lahore, Pakistan, from February 2019 to December 2020. A total of 180 pregnant women undergoing CS with SA were enrolled and randomly assigned to one of three groups: tramadol (T), ketamine (K), or placebo (P). The study-maintained uniformity in the demographic characteristics of all patients. The frequency and intensity of post-SA shivering were recorded, and these observations were compared among the three groups. The results of this study revealed significant differences among the three groups regarding the incidence and intensity of post-SA shivering. Shivering was observed in 33 (55.0%) patients in the ketamine (K) group, 12 (20%) in the tramadol (T) group, and 39 (65%) in the placebo (P) group (P = 0.0001). Tramadol demonstrated the highest efficacy in managing post-SA shivering, followed by a lower dosage of ketamine (K). The high incidence of shivering in the placebo group emphasized the necessity for preventive shivering management strategies in the context of CS under SA. Based on the results it can be concluded that the low-dose tramadol and ketamine are effective in reducing shivering frequency and intensity compared to a placebo. They can be considered as alternative options for nursing mothers who face challenges with pethidine. Proactive measures are recommended to manage post-SA shivering for better patient outcomes following CS under SA.